PENGARUH PERAN KOPERASI ANDALAN TERHADAP KESEJAHTERAAN ANGGOTA PETANI KELAPA SAWIT DI DESA BANJAR BALAM, KECAMATAN LIRIK, RIAU - Resti, Arin Riyanti; Yunianta, Yunianta; Mawardi, Nanang Kusuma (JURNAL ILMIAH AGRITAS, 2025)
This research aims to determine the role of cooperatives in the welfare of members in the Andalan Cooperative in Banjar Balam Village, Lirik District, Riau. This research was conducted using quantitative descriptive methods by distributing questionnaires to 40 members of oil palm farmers who are members of the Andalan Banjar Balam Village cooperative. The research results show that the role of the Andalan cooperative is in the role category, which is calculated by the total percentage of average achievement of 5 indicators of the cooperative's role (business partner, training provider, marketing facilitator, capital facilitator, motivator) of 83%. Then the welfare level of oil palm farmer members is already at prosperous stage II based on the 2021 BKKBN regulations. The regression coefficient shows Y= 2.069 + 0.198, meaning that there is a positive influence between the role of the Andalan cooperative on the welfare of oil palm farmer members.